Effect of High Current Density in Electrocoagulation Process for Sewage Treatment - Mohd, Nasrullah; Siddique, Md. Nurul Islam; Zularisam, A. W. (Asian J. Chem, 2014)
Treatment of sewage wastewater by electrocoagulation with high cell current densities (605 A/m2, 908 A/m2, 1211 A/m2, 1513 A/m2 and 1816 A/m2) using stainless steel, iron and aluminum electrodes were studied. High current densities applied were very effective for the removal of chemical oxygen demand, biochemical oxygen demand and suspended solid in 0.5 h. In the electrocoagulation of sewage wastewater, the effect of electrode material, current densities, electrocoagulation time, inter-electrode distance and initial pH were examined. The optimum operating range for each operating variable was experimentally determined in order to provide an economical and effective treatment for the sewage wastewater. Therefore, the optimum condition for this treatment is in 0.5 h, by using stainless steel electrode, at 1816 A/m2, in pH 7 and 10 mm electrode distances. The optimum treatment condition reduced chemical oxygen demand by 98.07 %, biochemical oxygen demand by 98.07 % and suspended solid by 97.64 % and the anode loss during the experiment was 9.2 × 102 g.